2012
DOI: 10.1111/j.1601-0825.2012.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of oral microbiota in jawbone samples of bisphosphonate‐related osteonecrosis of the jaw

Abstract: This study using limited sample size indicated that the jawbone associated with BRONJ was heavily colonized by specific oral bacteria and there were apparent differences between the microbiota of BRONJ and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 65 publications
8
38
0
5
Order By: Relevance
“…The importance of bacterial biofilm formation in the pathogenesis of BRONJ was reported previously, but the mechanisms responsible for bacterial colonization of denuded bone in patients on BPs were unclear (Sedghizadeh et al, 2008;Kos et al, 2010;Wei et al, 2012). Based on our experiments, one may suppose that BP-mediated bacterial adhesion plays an important role in this process.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 58%
See 2 more Smart Citations
“…The importance of bacterial biofilm formation in the pathogenesis of BRONJ was reported previously, but the mechanisms responsible for bacterial colonization of denuded bone in patients on BPs were unclear (Sedghizadeh et al, 2008;Kos et al, 2010;Wei et al, 2012). Based on our experiments, one may suppose that BP-mediated bacterial adhesion plays an important role in this process.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 58%
“…There are reports confirming an increased infection rate in these patients with bacterial species known to be etiological factors of bone infections (Sedghizadeh et al, 2008;Wei et al, 2012). System for testing bacterial adherence under flow conditions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Although bisphosphonates have seen clinical efficacy in a variety of pathologies, such as cancer metastases, multiple myeloma, Paget's disease of the bone, and osteoporosis, they can also cause serious side effects, most notably osteonecrosis of the jaw [1]. Given the high affinity of bisphosphonates for bone, some hypothesize that the accumulation of intravenously administered bisphosphonates in bone can lead to later necrosis of soft tissue and bone in the mandible and maxilla, especially following dental procedures [1,23,24]. As seen in Fig.…”
Section: Pleiotropic Effects Of Statinsmentioning
confidence: 99%
“…19,20,24 The presence of bacterial biofilms, most commonly, Actinomyces at BRONJ sites, has been demonstrated by histomorphometric and histological studies. 6,10,25,26,27,28,29 Our previous studies, for the first time, using 16S rRNA sequencing, have shown the presence of polymicrobial communities, both cultivable and uncultivable, in a broader perspective in the soft tissues 19 and jaw bone 24 sites of BRONJ lesions which otherwise, could go undetected by histomorphometric or histopathological analyses. Nevertheless, the ubiquitous influence of bacterial biofilms at the site of BRONJ lesions may impact the pathogenesis of BRONJ.…”
Section: Introductionmentioning
confidence: 99%